Spatiotemporal Analysis of Health Service Coverage in the Philippines - Clarisa Joy A. Flaminiano; Vicente Alberto R. Puyat; Victor Andrew A. Antonio; Jhanna Uy; Valerie Gilbert Ulep (Philippine Institute for Development Studies (PIDS), 2022)
We conducted a spatiotemporal analysis of trends and disparities in health service coverage indicators using PhilHealth data on insurance claims, membership, and accredited facilities merged with auxiliary datasets from the Department of Health and Philippine Statistics Authority. The results emphasize clear disparities in population coverage, facility coverage, service coverage, and financial protection across different subpopulations.
Keywords: 330; universal health care; health service coverage; spatiotemporal analysis; PhilHealth; equity